Worldviews of aspiring powers domestic foreign policy debates in China, India, Iran, Japan and Russia - Nau, Henry R., 1941-; Ollapally, Deepa Mary. (Oxford : Oxford University Press, 2013)
This title provides a serious study of the domestic foreign policy debates in five world powers who have gained more influence as the US's has waned: China, Japan, India, Russia and Iran. Featuring a leading regional scholar for each essay, they identify the most important domestic schools of thought - nationalists, realists, globalists, idealists/exceptionalists - and connects them to the historical and institutional sources that fuel each nation's foreign policy experience.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Nov. 13, 2012).
Keywords: Middle powers -- History -- 21st century; International relations -- Philosophy -- History -- 21st century; International relations -- History -- 21st century